Le roi, son favori et les baronset XVe siècles Légitimation et délégitimation du pouvoir royal en Angleterre et en France aux XIVe - Bilestone, Djro (Pariser Historische Studien, 2021)
At the end of the Western Middle Ages, the new notions of the legitimacy of royal power and its exercise were made more visible by the presence of royal favourites whose figure should be reconsidered. The present study links the reproach of sexual misconduct as a political argument in medieval discourse to medieval ideas about royalty and government, opening new perspectives of a cultural history of politics in the Later Middle Ages.